2007
DOI: 10.1002/bit.21259
|View full text |Cite
|
Sign up to set email alerts
|

Cardosins: A new and efficient plant enzymatic tool to dissociate neuronal cells for the establishment of cell cultures

Abstract: In the present work, we examined the feasibility of using cardosins, plant aspartic-proteinases from Cynara cardunculus L., to isolate cells from rat embryonic brain. Using morphological and functional assays, we compared cell cultures obtained with cardosins with those prepared with a well-established trypsin protocol. Cardosins and trypsin dissociation produced cells with similar yield, viability, and GABA release in response to a depolarizing stimulus. However, cardosins-dissociated cells appeared to recove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 19 publications
0
9
0
2
Order By: Relevance
“…Actually, as shown in Fig. 1, neurons isolated with cardosins and cultured for 24 h after plating consistently exhibited longer neurites (50±6.0 mm, P≤ 0.01), compared to the cultures of cells dissociated with trypsin (35.0±4.0 mm, P≤0.01), but the differences were no longer apparent in cells cultured for longer periods of time (Duarte et al 2007). …”
Section: Expression and Activity Of Ecm Proteins In Neuronal Culturesmentioning
confidence: 73%
See 4 more Smart Citations
“…Actually, as shown in Fig. 1, neurons isolated with cardosins and cultured for 24 h after plating consistently exhibited longer neurites (50±6.0 mm, P≤ 0.01), compared to the cultures of cells dissociated with trypsin (35.0±4.0 mm, P≤0.01), but the differences were no longer apparent in cells cultured for longer periods of time (Duarte et al 2007). …”
Section: Expression and Activity Of Ecm Proteins In Neuronal Culturesmentioning
confidence: 73%
“…These neurons exhibit normal morphology and function when compared to cultures prepared by the widely used trypsin dissociation method. This new protocol, when compared to the classic protocol, shows an improvement on neuronal recovery after cell plating, suggesting that cardosin dissociation of brain tissue is less aggressive to neurons than trypsin (Duarte et al 2007). As a matter of fact, we showed that cells isolated with cardosins appear to recover faster than those isolated with trypsin, as assessed by the number and length of neurites.…”
mentioning
confidence: 71%
See 3 more Smart Citations